2021
DOI: 10.1093/cvr/cvab245
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptide receptor B maintains heart rate and sinoatrial node function via cyclic GMP-mediated signalling

Abstract: Aims Heart rate (HR) is a critical indicator of cardiac performance that is determined by sinoatrial node (SAN) function and regulation. Natriuretic peptides, including C-type NP (CNP) have been shown to modulate ion channel function in the SAN when applied exogenously. CNP is the only NP that acts as a ligand for natriuretic peptide receptor-B (NPR-B). Despite these properties, the ability of CNP and NPR-B to regulate HR and intrinsic SAN automaticity in vivo, and the mechanisms by which it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Furthermore, we sought to assess the contributions of changes in ANS activity as well as intrinsic SAN function to the fractal structure of the HRV. Initially, we used time and frequency domain analysis to demonstrate changes in HRV during ANS blockade in vivo as well as in isolated atrial preparations and Frontiers in Physiology frontiersin.org isolated SAN myocytes, that are typical of those shown in previous studies (Moghtadaei et al, 2017;Dorey et al, 2020;Dorey et al, 2021;Dorey et al, 2022). However, nonlinear HRV analysis using MSMFDFA provided additional insight not possible with traditional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we sought to assess the contributions of changes in ANS activity as well as intrinsic SAN function to the fractal structure of the HRV. Initially, we used time and frequency domain analysis to demonstrate changes in HRV during ANS blockade in vivo as well as in isolated atrial preparations and Frontiers in Physiology frontiersin.org isolated SAN myocytes, that are typical of those shown in previous studies (Moghtadaei et al, 2017;Dorey et al, 2020;Dorey et al, 2021;Dorey et al, 2022). However, nonlinear HRV analysis using MSMFDFA provided additional insight not possible with traditional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, natriuretic peptides (including CNP) and their cognate receptors were shown to modulate ion channel function in the SAN [ 138 , 139 , 140 ]. Recently, to investigate the physiological roles of NPR-B signaling in regulating heart rate and SAN function, NPR-B-deficient mice were used, and it was revealed that NPR-B plays an essential physiological role in maintaining normal heart rate and SAN function by modulating ion channel function in SAN myocytes via a cGMP/PDE3/cAMP signaling mechanism [ 141 ].…”
Section: Effects Of Cnp On Heart Rate and Electrical Conduction In Th...mentioning
confidence: 99%
“…Therefore, maintaining an optimal heart rate is very important. Recently, Dorey et al evaluated HR regulation and sinoatrial node (SAN) function in heterozygous GC-B KO mice, which exhibit a slow HR, increased corrected SAN recovery time, and slowed SAN conduction, without evidence of cardiac hypertrophy or a change in cardiac function [ 40 ]. Hyperpolarization activated currents ( I f ) and L-type Ca 2+ currents ( I CaL ) were reduced due to lower levels of cGMP and the increased hydrolysis of cAMP by phosphodiesterase III (PDE III) in the SAN.…”
Section: Role Of Cnp In the Pathophysiology Of The Heartmentioning
confidence: 99%
“…The application of 8-Br-cGMP, an analog of cGMP, restored the I f and I CaL as well as SAN conduction. These data suggest that GC-B signaling is involved in the maintaining of normal HR and SAN function via the cGMP/PDE III/cAMP signaling mechanism [ 40 ].…”
Section: Role Of Cnp In the Pathophysiology Of The Heartmentioning
confidence: 99%